The utilisation of digital tools on ESL learners’ creativity: A systematic literature review - Joseph, Brennen Sta Maria; Hafizoah, Kassim; Ruhil Amal, Azmuddin (2022)
In order to effectively incorporate the use of digital tools, educators should consider how digital tools influence student learning, most importantly ESL learners’ creativity. Existing research suggests that digital tools can help ESL learners be more creative, but new research in this area has yet to be assessed. This systematic literature review attempts to identify and synthesise journal articles on the use of digital tools in the fields of creativity and education. To this end, journal articles was reduced to 13 relevant papers from an initial sample of 207 journal articles. The journal articles were assessed to arrive at a clear understanding of the state of research. Analysis reveals a positive outcome on the use of digital tools on ESL learners’ creativity. Findings conclude that research related to digital tools and creativity has dealt with major concerns in the field overall. Notably, additional research on the impact of digital tools on creativity in ESL education is recommended. The synthesis will be of interest to both researchers and practitioners in the field of creativity and education, concerning the use of digital tools.